Does School Connectedness Mitigate the Effects of Homelessness on Adolescent Well-Being? - Sheri Jenkins Keenan; Jane C Daquin (Children & Schools, 2026)
Abstract Youth homelessness in the United States remains a critical issue, each year affecting an estimated 4.2 million individuals ages 13 to 25. This study examines how homelessness influences adolescent physical, emotional, social, and academic well-being and whether school connectedness helps lessen these effects. Using data from the nationally representative 2021 Youth Risk Behavior Surveillance Survey of 8,527 high school students, binary logistic regression was used to analyze relationships between homelessness, feelings of closeness at school, and multiple well-being outcomes. Most students reported feeling close to others at school, suggesting social connectedness as a potential protective factor. Results indicated that homelessness significantly increased the likelihood of substance use, including alcohol (odds ratio [OR] = 3.661, p < .001). Conversely, school connectedness was associated with reduced odds of poor mental health (OR = 0.456, p < .001), demonstrating a clear protective effect for emotional well-being. However, interaction terms between homelessness and school connectedness were not statistically significant, indicating that connectedness does not fully mitigate adverse outcomes. These findings highlight the severe implications of homelessness for adolescents, particularly regarding substance use and mental health, and suggest that while school connectedness supports emotional well-being, additional interventions are needed to address broader risks.